Experimental optical and structural properties of ZnS, MgF2, Ta2O5, Al2O3 and TiO2 deposited by electron beam evaporation for optimum anti-reflective coating designs. (1st September 2022) - Li, Brian; Gabás, Mercedes; Ochoa-Martínez, Efraín; de la Cruz, Víctor González; López-Escalante, Mari Cruz; León-Reina, Laura; Peña, Rafael; García-Díaz, Pilar; García, Iván; Algora, Carlos
Highlights: MgF2, ZnS, Ta2 O5, Al2 O3 and TiO2 refractive indexes as a function of thickness. Ta2 O5, Al2 O3 and TiO2 refractive indexes as a function of O2 flow. Refractive indexes validated against experimental reflectance and transmitance data. Impact on the optimization of ARC thicknesses for III-V multijunction solar cells. Abstract: MgF2, ZnS, Ta2 O5, Al2 O3 and TiO2 are some of the most common dielectric materials actually used in solar cells as anti-reflective coatings. For such purpose, they have been deposited by electron beam evaporation, which is one of the preferred technique in industrial settings. In this work we aim to understand the relationship between their optical and physical properties and deposition parameters and thicknesses, being spectroscopic ellipsometry the main technique used for such issue. MgF2 and ZnS have demonstrated rather good optical quality except for the thinnest samples. For Ta2 O5, O2 flow during growth has been revealed as critical parameter for ensuring the proper composition of the layer. Al2 O3 samples showed a very important amount of Al hydroxide, which is detrimental of the optical quality of these layers. TiO2 samples have also contamination problems, in this case due to oxygen species and Ti 3+ oxide presence. For all these oxides, optical properties are clearly influenced by layer thickness. The layer optical parameters n and k have been determined as a function of wavelength (300–1800 nm) and validated against experimental reflectance and transmittance data. Finally, the impact that the proper knowledge of n and k values have when designing broad-band anti-reflective coatings for III-V multijunction solar cells is quantified in terms of short-circuit current relative increase.